HUBUNGAN TINGKAT STRES DENGAN PERILAKU MEROKOK PADA REMAJA DI DESA BANJARGONDANG KEC. BLULUK, KAB. LAMONGAN - Hendra Setyoko, Kukuh; Puspita, Sylvie; Nuraminudin Aziz, Aditya (LPPM STIKES HUSADA JOMBANG, 2024)
Male adolescents experiencing stress are more likely to exhibit negative behaviors, which is smoking. The objective of this research is to assess the correlation between the level of stress and smoking behavior among teenagers in Banjargondang Village, Bluluk District, Lamongan Regency. The research design employed in this study is descriptive correlation using a cross-sectional approach. In this research, the population consists of 105 adolescents aged 18-22 years, and a sample of 42 respondents was chosen through purposive sampling method. Data was gathered through questionnaires on stress levels and smoking behavior, which were subsequently analyzed using chi-square analysis. The research findings indicate that the majority of respondents who have a moderate level of stress are 26 respondents (61.9%), and the majority of respondents who exhibit a moderate level of smoking habit are 28 respondents (66.7%). The chi-square test results demonstrate a relationship between the level of stress and smoking behavior among adolescents in Banjargondang Village, Bluluk Sub-District, Lamongan Regency, with a p-value (2-sided) of 0.000, which is less than α (0.05). There is a need for knowledge about the impact of stress and smoking habits on adolescents so that they have the ability to avoid the potential negative consequences of these two factors.